Development of scaffolding-based science e-modules to improve junior high school students’ scientific reasoning - Hanum, Wardah Nabilah; Nuha, Ulin; Ridlo, Zainur Rasyid (Universitas Muhammadiyah Mataram, 2024)
Scientific Reasoning is a high-level thinking ability to think scientifically, systematically, and logically in the scientific method process. The scientific reasoning of junior high school students is still low in Science learning. In fact, scientific reasoning is an essential component of the cognitive flow of 21st-century skills. This study aimed to describe the validity, practicality, and effectiveness of scaffolding-based Science e-module in improving the scientific reasoning of junior high school students. This study was a developmental study with the ADDIE model. The subjects were 35 7-E students in SMP Negeri 7 Jember with the implementation in the even semester of the 2023/2024 academic year. The data collection techniques used were observation, documentation, validation sheets, implementation observation sheets, tests (pretest and posttest), and questionnaires of student response. Based on the research results, the implementation of a scaffolding-based Science e-module obtained a validation value of 89.8%, which was included in the valid category and can be used in the learning process. The results of the practicality analysis obtained a value of 88%, which was included in the very practical category to be used in the learning process. The effectiveness was obtained from the results of the pretest and posttest with an N-Gain value of 0.73%, which was included in the high category, and the results of student response were 89.4%, which was included in the very good category and effective in improving scientific reasoning of the junior high school students.